Sistem Informasi Aplikasi Inventori pada Panti Sosial Bina Karya Wanita - Zulkarnain Siddik; Dali Santun Naga; Zyad Rusdi (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The purpose of this application development is to assist the process of recording and checking the goods data at the Panti Sosial Bina Karya Wanita. The method used in developing this application is SDLC (System Development Life Cycle).This application manages information about inventory at Panti Sosial Bina Karya Wanita. This application is built with PHP and utilizing MySQL as database management system. When goods are taken out or coming in, its barcode will be scanned and automatically calculated into the program. This program can also generate the printable monthly report like report of incoming goods, report of outcoming goods, report of good ordering, reports of good demanding, and report of returning goods.